Detection Rate, Recall Rate, and Positive Predictive Value of Digital Compared to Screen-Film Mammography in the Quebec Population-Based Breast Cancer Screening Program. Issue 4 (November 2016) - Théberge, Isabelle; Vandal, Nathalie; Langlois, André; Pelletier, Éric; Brisson, Jacques
Purpose: The study sought to compare performance indicators of computed radiography (CR) using different plate readers, digital direct radiography (DR), and screen-film mammography (SFM) in a population-based screening program. Methods: This analysis involved women 50-69 years of age who participated in the breast screening program of Quebec (Canada) and who had screening mammogram between January 1, 2007, and September 30, 2012. The detection rate, recall rate, and positive predictive value of CR (n = 672, 125 mammograms) and DR (n = 60, 023) were compared to SFM (n = 782, 894) using mixed-effect logistic regression, adjusting for potential confounders. No institutional review board approval was required. Results: CR was not associated with change in cancer detection rate (odds ratio [OR]: 0.95; 95% confidence interval [CI]: 0.88-1.03), but with a small increase in recall rate (OR: 1.03; 95% CI: 1.01-1.06) compared to SFM. The association of CR with recall rate varies with the CR plate reader manufacturer ( P < .0001). DR was not associated with change in detection rate (OR: 1.06; 95% CI: 0.89-1.25), but with an increase in the recall rate (OR: 1.25; 95% CI: 1.19-1.30) compared to SFM. Conclusions: In our screening program, digital mammograms gave detection rates equivalent to those of SFM, but with an increase of recall rate, particularly for DR. If this situation persists, the adoption of DR may increase the adverse effects of screening with little or no benefit for women.